DAMPAK ERUPSI GUNUNG MERAPI TERHADAP LAHAN DAN UPAYA-UPAYA PEMULIHANNYA - Rahayu, Rahayu; Ariyanto, Dwi Priyo; Komariah, Komariah; Hartati, Sri; Syamsiyah, Jauhari; Dewi, Widyatmani Sih (Universitas Sebelas Maret, 2014)
The eruption of Merapi mountain has primary and secondary hazard and may damage to the land. In detail, the hazards are land degradation is a loss of some or many of germplasm and changes in plant biodiversity. The others hazard including loss of water catchment areas, the destruction of forests, and even the closing of the water source, as well as the loss of water channels. The burried of soil and soil formation inhibition were caused by the repeated eruptions of Merapi, beside the loss of roads access to agricultural land and loss of land ownerships boundaries by the eruption and cool lava. Materials of eruption are sand and pyroclastic materials, as well as the nature of cementation require special techniques and technology to use the land as new farmland. Land restoration efforts can be done with the land management by reforestation on government-owned land for water catchment function, agroforestry forage grass based, grazing field on land owned by the village and residents, with the use of organic materials in the eruption sandy soil ameliorant.